Changes of the activity and expression of gamma-glutamylcysteine synthetase in patients with chronic obstructive pulmonary disease - Lin, Shu-dian; Dai, Ai-guo; Xu, Ping (Zhonghua jiehe he huxi zazhi, 2005)
To investigate the oxidative/antioxidative status in patients with chronic obstructive pulmonary disease (COPD), and to study the expression and location of gamma-glutamylcysteine synthetase (gamma-GCS) in lung tissues. (1) Serum samples of 13 patients with COPD in exacerbation and 9 healthy non-smokers were collected for measurements of the level of reduced glutathione (GSH), reactive oxygen species (ROS), total antioxidative capacity (T-AOC) and gamma-GCS activity. (2) Lung tissues from 22 patients (12 patients with COPD and 10 patients as control) undergoing resection for lung tumor were collected for study of the expression and location of gamma-GCS and gamma-GCS mRNA by immunohistochemistry and in situ hybridization, respectively. (1) Significantly decreased level of GSH [(23.87 +/- 3.86) mg/ml], increased level of ROS [(2 463 +/- 199) U/ml], decreased T-AOC [(5.34 +/- 0.22) U/ml] and enhanced activity of gamma-GCS [(19.22 +/- 3.36) U/ml] were shown in the serum of patients with an acute exacerbation of